A Novel View on the Role of Intracellular Tails in Surface Delivery of the Potassium-Chloride Cotransporter KCC2 - Friedel, Perrine (eNeuro, 2017)
A plethora of neurological disorders are associated with alterations in the expression and localization of potassium-chloride cotransporter type 2 (KCC2), making KCC2 a critical player in neuronal function and an attractive target for therapeutic treatment. The activity of KCC2 is determined primarily by the rates of its surface insertion and internalization. Currently the domains of KCC2 dictating its trafficking and endocytosis are unknown. Here, using live-cell immunolabeling and biotinylation of KCC2 proteins expressed in murine neuroblastoma N2a cells, human embryonic kidney 293 cells, or primary cultures of rat hippocampal neurons, we identified a novel role for the intracellular N and C termini in differentially regulating KCC2 surface expression. We report that the N terminus is required for KCC2 insertion into the plasma membrane, whereas the C terminus is critical for the membrane stability of KCC2. Our results provide novel insights into the structure–function role of specific KCC2 domains and open perspectives in exploring structural organization of this protein.